Tumor‐size‐based morphological features of metastatic lymph node tumors from primary lung adenocarcinoma. (30th October 2014) - Yamada, Eiji; Ishii, Genichiro; Aramaki, Nao; Aokage, Keiju; Hishida, Tomoyuki; Yoshida, Junji; Kojima, Motohiro; Nagai, Kanji; Ochiai, Atsushi
<x xml:space="preserve">Abstract</x> Most primary lung adenocarcinomas show histological diversity, however, histological diversity in the metastatic lymph node tumors (LNT) is not well defined. The aim of this study was to explore the histological characteristics of the metastatic LNT based on their sizes. We analyzed 163 primary tumors and 509 metastatic LNTs. When the primary tumor showed papillary‐predominant subtype, the most frequent histological subtype in the metastatic LNT that were ≤2 mm in diameter was solid subtype (49%), followed by papillary subtype (35%); on the other hand, in the metastatic LNT measuring >2 mm in size, the frequency of tumors showing papillary‐predominant subtype increased significantly to 52% (P = 0.04). When the primary tumor showed acinar‐predominant subtype, the most predominant subtype in the ≤2 mm metastatic LN tumors was acinar subtype (55%), followed by solid subtype (40%), with the frequency of acinar subtype increasing significantly to 76% in the metastatic LNT that were >2 mm in diameter (P = 0.04). These results indicate that solid subtype is the characteristic histological subtype in the early phase of the LN metastatic process, and that as the metastatic LNT grow larger, they develop morphological features resembling those in the primary tumor.